Hereditary arthro-ophthalmopathy (Stickler syndrome): a diagnosis to consider in familial premature osteoarthritis. - Rai, A; Wordsworth, P; Coppock, J; Zaphiropoulos, G; Struthers, G (1994)
A number of factors contribute to the pathogenesis of osteoarthritis. Genetic factors are predominant in some cases, including the syndrome of hereditary arthro-ophthalmopathy. The clinical features of the syndrome and the concept of genetic mutations in matrix components are discussed.